THE EFFECT OF MANAGEMENT CHARACTERISTICS ON EARNINGS MANAGEMENT THROUGH PERCEIVED AMBIGUITY IN ACCOUNTING STANDARDS - Suci, Patricia Paramitha; Fajar, Stella Marissa Permata (UI Scholars Hub, 2024)
We investigated the influence of management characteristics, specifically narcissism, impulsivity, construal mindset, and Machiavellianism, on perceived ambiguity toward accounting standards and the impact of perceived ambiguity toward accounting standards on earnings management tendencies. We surveyed 116 respondents from undergraduate, master's, and doctoral programs at various universities in Indonesia. We found that construal mindset, impulsivity, and Machiavellianism positively were related to perceived ambiguity toward accounting standards. Perceived ambiguity toward accounting standards has also been shown to affect earnings management tendencies positively. However, we did not find that narcissism was related to perceived ambiguity toward accounting standards. Additionally, we did not find that narcissism and construal mindset were positively related to earnings management tendencies when mediated by perceived ambiguity toward accounting standards. This research aims to provide a deeper understanding of how management characteristics influence earnings management practices.